An Analysis Colloquial Language of The Main Character by Lara Jean In “ To All The Boys I’ve Loved Before” Movie - Hasna Hasbullah; Hasanuddin Fatsah; Novriyanto Napu (Transbahasa, 2024)
This study investigates the use of colloquial language by the main character, Lara Jean, in the movie To All The Boys I've Loved Before. Employing a qualitative method, the analysis categorizes the character's utterances into eight types of colloquial language based on their distinct characteristics: Reduplication, Double Subject, Coinage, Compounding, Clipping, Pidgin-Induced Slang, Semantic Extension, and Contractions. A total of 79 instances of colloquial expressions were identified, showcasing the informal and dynamic nature of Lara Jean’s communication style. Each type of colloquialism contributes to the construction of Lara Jean’s relatable and personable character, enhancing her emotional depth and connection with the audience. For instance, the use of reduplication emphasizes emotions and ideas, while coinage and clipping reflect creativity and linguistic adaptability. This study emphasizes the role of colloquial language in shaping character identity, fostering realism, and engaging audiences. By analyzing the intricate ways in which colloquial language is woven into Lara Jean's dialogues, the research underscores its significance in the broader context of film and literary studies, particularly in illustrating informal communication's impact on storytelling. These findings contribute to understanding how language usage enhances character portrayal and narrative relatability, making this study relevant for linguistics, media, and cultural analysis.